A case of hypertrophic cardiomyopathy with previous aortic valve replacement - Hongyan Xiao; Laichun Song; Meng Guo; Liang Tao (Journal of Cardiothoracic Surgery, 2024)
Abstract We describe a 45-year-old patient who was diagnosed with hypertrophic obstructive cardiomyopathy (HOCM) after the aortic valve replacement surgery. Enlarged left atria, thickened ventricular septum, left ventricular outflow tract stenosis, moderate mitral regurgitation and mild tricuspid regurgitation in the echocardiography were found. We offered the patient the new minimally invasive treatment modality: percutaneous intra-myocardial septal radiofrequency ablation (PIMSRA). We demonstrate the safety and efficacy with pictures. One month after surgery, the patient recovered well with improved symptoms of chest tightness, and no LVOT obstruction or arrhythmia.